2013
DOI: 10.1111/jopr.12072
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Clasp Design on Retention at Different Intervals Using Different Abutment Materials and in a Simulated Oral Condition

Abstract: (1) The back-action clasp maintains its retention force for a longer period than the circlet (E) clasp. (2) Composite resin contouring of teeth provided retention comparable to enamel and a ceramic material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…Loss of retention of the clasps due to fatigue resistance test was considered as a good indicator of permanent deformation of the clasps (3) . These agreed with Helal, et al who reported that the clasp may lose its retention force as a result of multiple deflections (12) , and contradict with Meenakshi, et al who showed that the retention force of acetal clasps did not decrease after cycling intervals while the Co-Cr clasps lost retention force within 730 cycles of insertion/removal and continued to lose retention force during the remaining intervals (23) .This may be explained by the method which is used to carry out the test.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Loss of retention of the clasps due to fatigue resistance test was considered as a good indicator of permanent deformation of the clasps (3) . These agreed with Helal, et al who reported that the clasp may lose its retention force as a result of multiple deflections (12) , and contradict with Meenakshi, et al who showed that the retention force of acetal clasps did not decrease after cycling intervals while the Co-Cr clasps lost retention force within 730 cycles of insertion/removal and continued to lose retention force during the remaining intervals (23) .This may be explained by the method which is used to carry out the test.…”
Section: Discussionsupporting
confidence: 91%
“…The test conditions were maintained at room temperature (25 ± 2˚C) and wet condition. Removal and insertion cycling of clasps was carried out for 360, 730, 1080, 1440, 2116 and 2880 cycles (corresponding to 3,6,9, 12, 18 and 24 months of simulated clinical use of a RPD) to simulate the fatigue resistance test (12) . Using Universal testing machine running at 5 mm/ min the retention force was determined for the clasp at 360, 730, 1080, 1440, 2116 and 2880 cycles, and recorded by the computer software (Bluehill, Instron instruments).…”
Section: Testing Conditionsmentioning
confidence: 99%
“…(19)(20)(21)(22) Therefore, the present study was conducted to assess the influence of different staining beverages on the color stability of two newly introduced thermoplastic Acetal resin tooth-colored clasp materials by scanning spectrophotometer at different immersion periods. (23,24) Retentive clasp arms must be capable of flexing and returning to their original form .also , must be minimize the stresses on the abutment as much as possible and prevent permanently distorted during service in addition to provide good aesthetic results (25)(26)(27) In this in vitro study the two different materials were used Group A: polyoxymethylene (Acetal) and Group B: polyamide (Bre-flex 2nd edition) for construction RPD esthetic clasp and denture base.…”
Section: Discussionmentioning
confidence: 99%
“…Cast clasps were planned, since rigid direct retainers are associated with less mobility of the abutment teeth and less force on the residual ridge than wrought‐wire retainers . Back‐action clasps with mesial rests were used on premolar teeth bilaterally to provide more retention and stability from their long arms . It has also been found that back‐action clasps can maintain their retentive force for a longer period .…”
Section: Clinical Reportmentioning
confidence: 99%
“…Back‐action clasps with mesial rests were used on premolar teeth bilaterally to provide more retention and stability from their long arms . It has also been found that back‐action clasps can maintain their retentive force for a longer period . Mesial rests were used to reduce stress on the abutment teeth in the distal‐extension RPD.…”
Section: Clinical Reportmentioning
confidence: 99%